C.-2 and -11 that would be the answer.
Answer:
f(y) = 12 + 4x
Step-by-step explanation:
Output is 12 more than 4 timea the input
The dependent variable = y
The dependent variable = x
The input is the independent variable, x
Output is the dependent variable, y
Output = 12 + (4 * input)
Hence, the function rule can be written has :
f(y) = 12 + 4x
<h3>Given</h3>
1 (female) pharmacist counting prescriptions at the end of the day
(prescriptions for antibiotics) = (7/4)×(prescriptions for tranquilizers)
33 = (prescriptions for tranquilizers) + (prescriptions for antibiotics)
<h3>Find</h3>
The number of (prescriptions for tranquilizers)
<h3>Solution</h3>
Let <em>x</em> represent the number of <em>prescriptions for tranquilizers</em>. Then the number of prescriptions for antibiotics is (7/4)x, and the total number of prescriptions is
... 33 = x + (7/4)x . . . . . . . . . . put the given information in the given relation
... 33 = (4/4)x + (7/4)x . . . . . . rewrite 1 as 4/4 so we can add to 7/4
... 33 = ((4+7)/4)x = (11/4)x . . . simplify
... 33×(4/11) = (4/11)×(11/4)x . . . multiply by the reciprocal of the coefficient of x
... 12 = x . . . . . . . . . . . . . . . . . simplify
The pharmacist had 12 prescriptions for tranquilizers.
The pharmacist had 33-12 = 21 prescriptions for antibiotics.
There was 1 pharmacist and 33 prescriptions.
Answer:
Step-by-step explanation:
<h3>#6</h3>
<u>Given equation:</u>
- 4/(x - 3) + 2/(x - 2) = 2
<u>Multiply all terms by (x - 3)(x - 2):</u>
- 4(x - 2) + 2(x - 3) = 2(x - 3)(x - 2)
- 2(x - 2) + (x - 3) = (x - 3)(x - 2)
- 2x - 4 + x - 3 = x² - 5x + 6
- x² - 5x - 3x + 6 + 7 = 0
- x² - 8x + 13 = 0
- x = (8 ± √(8² - 4*13))/2 = (8 ± √12)/2 = (8 ± 2√3)/2 = 4 ± √3
<u>Compare this to the given form to get:</u>
Correct choice is A
The answer is 2 just put it in your calculator